Four new Myrcia (Myrtaceae) from Amazonian Brazil - Sobral, Marcos; de Souza, Maria Anália Duarte; Santos, Matheus Fortes (Phytotaxa, 2019)
There are described and illustrated Myrcia caloneura, M. oreophila, M. sticta and M. tarauacana. Myrcia caloneura, from the states of Amazonas and Pará, is related to M. rugosior, but differs by its adult glabrescent blades and tetramerous flowers; M. oreophila, from the state of Roraima,is related to M. aegiphiloides, but has pilose, loosely reticulate blades and pilose flowers; M. sticta, from the state of Amazonas, is close to M. splendens, but has blades with rounded to cordate base and larger and easily visible glandular dots, and M. tarauacana is related to M. aequatoriensis and M. crassimarginata but has shorter blades and longer inflorescences. Conservation status of each species is also suggested.